Environmental Behavior, Sources, and Effects of Chlorinated Polycyclic Aromatic Hydrocarbons - Ohura, Takeshi (ScientificWorldJournal, 2007)
The environmental sources and behaviors of chlorinated 2- to 5-ring polycyclic aromatic hydrocarbons (ClPAHs). ClPAHs are ubiquitous contaminants found in urban air, vehicle exhaust gas, snow, tap water, and sediments. The concentrations of ClPAHs in each of these environments are generally higher than those of dioxins but markedly lower than the concentrations of the parent compounds, PAHs. Environmental data and emission sources analysis for ClPAHs reveal that the dominant process of generation is by reaction of PAHs with chlorine in pyrosynthesis. This secondary reaction process also occurs in aquatic environments. Certain ClPAHs show greater toxicity, such as mutagenicity and aryl hydrocarbon receptor activity, than their corresponding parent PAHs. Investigation of the sources and environmental behavior of ClPAHs is of great importance in the assessment of human health risks.